2005
DOI: 10.1097/01.shk.0000168871.60531.6f
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Hypothermia Protects Against Systemic Oxidative Stress in a Rat Model of Intestinal Ischemia and Reperfusion Injury

Abstract: Multisystem organ failure represents a major cause of mortality in intestinal ischemia and reperfusion (I/R), and oxidative stress plays a key role in its pathogenesis. Hypothermia is beneficial in I/R injury, but its effects on systemic oxidative stress have not been elucidated. The aim of this study was to evaluate the effects of moderate hypothermia on systemic oxidative stress after intestinal I/R injury. Anaesthetized adult rats (n = 10 per group) underwent 60 min of intestinal ischemia followed by 120 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 36 publications
1
42
1
2
Order By: Relevance
“…5,31 In our study, intestinal I/R injury was associated with a significant decrease of SOD activity, a major endogenous antioxidant enzyme, and increase of the lipid peroxidation product MDA in the injury group. Treatment with propofol increased SOD activity and attenuated MDA production that was associated with a reduced Chiu's score (Table).…”
Section: Discussionmentioning
confidence: 91%
“…5,31 In our study, intestinal I/R injury was associated with a significant decrease of SOD activity, a major endogenous antioxidant enzyme, and increase of the lipid peroxidation product MDA in the injury group. Treatment with propofol increased SOD activity and attenuated MDA production that was associated with a reduced Chiu's score (Table).…”
Section: Discussionmentioning
confidence: 91%
“…Support for this theory is provided by the observation that ischemic injury to the small bowel is most severe at the tip and is attenuated by intraluminal perfusion with oxygenated saline 26 . A variety of associations between ascorbic acid and IR injury has been described recently [27][28][29][30][31] . Cizova et al 27 demonstrated that the ascorbic and uric acid concentrations increased generally after IR in comparison to intact controls, but this increase was not sufficient to prevent lipid peroxidation in serum and intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma malondialdehyde (MDA), a measure of lipid peroxidation, was measured by high-performance liquid chromatography (33). Plasma TGs were measured spectrophotometrically (Sigma Chemical Co.) and nonesterified fatty acids (NEFAs) were measured by a spectrophotometric kit (Wako Chemical Company).…”
Section: Methodsmentioning
confidence: 99%